2013
DOI: 10.7554/elife.00780
|View full text |Cite
|
Sign up to set email alerts
|

Minor introns are embedded molecular switches regulated by highly unstable U6atac snRNA

Abstract: Eukaryotes have two types of spliceosomes, comprised of either major (U1, U2, U4, U5, U6) or minor (U11, U12, U4atac, U6atac; <1%) snRNPs. The high conservation of minor introns, typically one amidst many major introns in several hundred genes, despite their poor splicing, has been a long-standing enigma. Here, we discovered that the low abundance minor spliceosome’s catalytic snRNP, U6atac, is strikingly unstable (t½<2 hr). We show that U6atac level depends on both RNA polymerases II and III and can be rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
102
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 47 publications
8
102
1
Order By: Relevance
“…However, recent findings suggest that regulation of U12-type splicing may be more complicated than previously thought. For example, p38MAPK-mediated up-regulation of the otherwise rate-limiting levels of U6atac in HeLa cells appears to constitute a sophisticated regulatory mechanism to facilitate the rapid mobilization of critical U12-type intron-containing transcripts in response to growth stimuli (14). Because many of these transcripts encode genes with functions in mRNA production, such an amplification of U12-type splicing activity is likely to generate a robust transcriptome-wide response.…”
Section: Rnpc3 Deficiency Leads To a Pleiotropic Phenotype In Developingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent findings suggest that regulation of U12-type splicing may be more complicated than previously thought. For example, p38MAPK-mediated up-regulation of the otherwise rate-limiting levels of U6atac in HeLa cells appears to constitute a sophisticated regulatory mechanism to facilitate the rapid mobilization of critical U12-type intron-containing transcripts in response to growth stimuli (14). Because many of these transcripts encode genes with functions in mRNA production, such an amplification of U12-type splicing activity is likely to generate a robust transcriptome-wide response.…”
Section: Rnpc3 Deficiency Leads To a Pleiotropic Phenotype In Developingmentioning
confidence: 99%
“…Since its discovery two decades ago, the existence of this highly conserved, second splicing pathway has been an intriguing aspect of gene expression. Interestingly, U12-type introns are nonrandomly distributed across the genome (11) and their removal is thought to be rate-limiting in the generation of mature mRNAs (12)(13)(14).Aberrant splicing is the basis of many human diseases and up to one-third of disease-causing mutations may lead to splicing defects (15). Although the majority of these defects occur in U2-type introns and splicing factors, perturbations in U12-type splicing have also been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is known that retention of a minor class intron generally leads to degradation of the transcript. 17 The reason for the existence of 2 different spliceosomes is not entirely understood, but it has been suggested that the minor spliceosome acts in the cytoplasm to avoid dependence on a functioning nucleus. This has 1 major advantage; when during cell division, the nuclear envelope breaks down, minor splicing is still available.…”
mentioning
confidence: 99%
“…19 Interestingly, it was recently shown that usage of the minor spliceosome is rapidly increased by the activation of cell-stress activated kinase p38 mitogen-activated protein kinase (MAPK) through stabilization of U6atac. 17 This resulted in increased expression of hundreds of minor intron-containing genes. Because mRNAs with retained minor introns are often degraded through the nonsense-mediated decay (NMD) pathway (Figure 2A), the activation of p38 MAPK may trigger minor spliceosome usage and thus control gene expression in response to stress.…”
mentioning
confidence: 99%